2010
DOI: 10.1161/circresaha.110.217299
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Mechanisms of T-Lymphocyte Activation and Vascular Inflammation Produced by Angiotensin II–Induced Hypertension

Abstract: T he CNS plays an integral role in blood pressure regulation, primarily through sympathetic activation and mediation of various neurohumoral factors such as angiotensin II (Ang II) and vasopressin. [1][2][3][4] Hormones such as these can access the circumventricular organs, which are adjacent to the cerebral ventricles and have a poorly formed blood brain barrier. The circumventricular organs implicated in blood pressure control include the organum vasculosum of the lamina terminalis (OVLT), the area postrema,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
247
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(264 citation statements)
references
References 25 publications
15
247
0
2
Order By: Relevance
“…Hydralazine was chosen based on its antihypertensive properties of lowering blood pressure in a dose-dependent manner without acting on AngII receptors. 24,25 RAS upregulation was demonstrated in the animals that received AngII+hydralazine, as evidenced by a significant elevation in serum aldosterone, which is a downstream mediator and marker of RAS activation. Our primary observation using this model was that the addition of hydralazine to AngII resulted in normalization of the blood pressure and inhibition of the fibrosis that is normally seen in animals receiving AngII.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hydralazine was chosen based on its antihypertensive properties of lowering blood pressure in a dose-dependent manner without acting on AngII receptors. 24,25 RAS upregulation was demonstrated in the animals that received AngII+hydralazine, as evidenced by a significant elevation in serum aldosterone, which is a downstream mediator and marker of RAS activation. Our primary observation using this model was that the addition of hydralazine to AngII resulted in normalization of the blood pressure and inhibition of the fibrosis that is normally seen in animals receiving AngII.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings are in keeping with other studies that have suggested that the effects of AngII on fibrosis are blood pressure dependent. 24,25,39 Some reports have even suggested that blood pressure can affect the migration of fibrocytes (CD45 + /SMA + ) into the myocardium, but these reports did not elucidate a definitive mechanism. 25 In contrast, transgenic mice that overexpress the AT1a receptor and develop hypertrophy and fibrosis do so without developing hypertension, emphasizing the multifactorial pathways capable of promoting extracellular matrix deposition and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic nervous system innervates both primary (thymus, bone marrow) and secondary tissues and lymphoid tissues (spleen, lymph nodes), and most immune cells express receptors for neurohormones and catecholamines. 16 Inhibition of the NADPH oxidase subunit p22 phox in the subfornical organ eliminated the Ang II-induced hypertensive response and vascular inflammation. 17 In addition, a peripheral neuroimmune response in the spleen, mediated by celiac ganglion efferent nerve fibers, is essential for the development of hypertension.…”
Section: Complementmentioning
confidence: 99%
“…88,123,124 T-lymphocytes appear particularly critical for Ang II and deoxycorticosterone acetate-salt-induced hypertension and the concomitant vascular and kidney dysfunction. 121,122,125 T-cell activation is increased by Ang II and leads to the production of pro-inflammatory cytokines. 121 Intriguingly, anti-TNFa therapy (etanercept) has been shown to prevent Ang II-induced hypertension and vascular oxidative stress.…”
Section: Drug-resistant Hypertension-how To Treat?mentioning
confidence: 99%